Pheidole Westwood, 1839 (Hymenoptera, Formicidae) of Madagascar - an introduction and a taxonomic revision of eleven species groups - Sebastian Salata (ZooKeys, 2020)
In the global scale, the genus Pheidole Westwood, 1839 is one of the most diverse ant genera. However, very little is known about the Pheidole fauna of Madagascar - an island considered as a global biodiversity hotspot. Most of the data describing the diversity of this genus on the island can be found in a number of short faunistic notes in majority originating in the late 1800s. The last Madagascar Pheidole species was described more than 100 years ago. Thanks to comprehensive inventories conducted across the island the Pheidole collection deposited at the California Academy of Sciences contains more than 50,000 specimens from almost 4,500 localities. This material, combined with type specimens deposited in Museum d'Historie Naturelle, Geneva, was used as a base for a taxonomic review of this genus. Here we present an introduction to Pheidole of Madagascar, define 16 species groups, containing approximately 140 species, and revise eleven of them. The monograph also includes keys to species groups, and 52 species - members of groups revised in this monograph. This publication is meant to be the first in a series aiming to revise the taxonomy of all Pheidole in Madagascar.